Implications of civil procedure law reform on judicial practice - Yasin, Husain N (Institute Of computer Science (IOCS), 2025)
In order to address the persistent issues of complexity and inefficiency in Indonesia's judicial system, reforms to civil procedural legislation aim to enhance accessibility and streamline processes. This study examines the effectiveness of these reforms, focusing on challenges such as overly formal procedures and insufficient human and technological resources, using a normative descriptive and juridical-analytical methodology. The findings highlight the positive impact of innovations like e-court systems in simplifying litigation processes, though the success of these reforms hinges on addressing technical infrastructure, enhancing judicial human resource capabilities, and fostering a transformative shift in legal culture. Practical implications of this research include providing actionable insights for policymakers to prioritize investments in technology and training, ensuring that procedural reforms benefit all societal segments, including rural and marginalized communities. The study contributes to the justice system by offering a blueprint for creating a more inclusive, efficient, and people-centered judiciary in Indonesia, fostering greater public trust and procedural fairness.